FACTORS AFFECTING EATING BEHAVIORS AND PHYSICAL ACTIVITY IN THAI BUDDHIST MONKS - Lutthapinun, Nutthapong; Sukonthasab, Suchitra (Journal of Sports Science and Health, 2020)
Purpose : This research were to study the eating behaviors and physical activity in Thai Buddhist monks and to determine factors affecting of eating behaviors and physical activity in Thai Buddhist monks. Methods : This study was a survey research. The subjects in this study consisted of 500 Buddhist monks in Thailand, based on MultiStage Random Sampling. The questionnaires were created by the researcher with a content validity of 0.83. Data were analyzed using frequency, percentages, means, and standard deviation. Multiple regression was used to determine the factors affecting eating behaviors and physical activity in Thai Buddhist monks at the significance level of 0.05 Results : Thai Buddhist monks has an average overall eating behaviors and physical activity in moderate level (x=1.85, SD=0.29). Predisposing factor affecting attitude toward eating behaviors and physical activity, reinforcing factor of eating behaviors and physical activity, and enabling factor of eating behaviors and physical activity were able to predict 25.4 percent of explained variables (R2=0.254) at the significance level of 0.05. Predisposing factor toward attitude affected eating behavior and physical activity in Thai Buddhist monks the most (Beta=0.273). Conclusion : Buddhist monks in Thailand had an eating behaviors and physical activity in moderate level. Predisposing factor toward attitude affected eating behaviors and physical activity in Thai Buddhist monks more than other factors. Therefore, health-related organizations should focus on adjusting attitude toward Thai Buddhist monks’ health care.